Azerbaijan Transport Sector 2011 - Irina Tochitskaya (Center for Social and Economic Research (CASE), 2012)
The report evaluates progress achieved in implementation of structural reforms of the transport sector in Azerbaijan in the following subsectors: railways, road transport and roads, air transport and airports, maritime transport and ports. It presents standardized and qualitative indicators that assess the level of the transport sector reforms in three areas: 1) commercialization and privatization, 2) tariff policy, and 3) institutional and regulatory changes. The aggregated index is calculated on the basis of the 21 indicators that reflects the status of the reforms in each sector at a period under review.
Keywords: L91; L92; L93; R4; O18; P21; 330; Transportation analysis; Transition economies; Reform; Verkehrsgewerbe; Verkehrsinfrastruktur; Reform; Aserbaidschan